(untitled) (Studia Prawnicze / The Legal Studies, 2010)
Obraz postępowania dowodowego w odwoławczym stadium procesu karnego uzależniony jest ściśle od przyjętego w danym systemie procesowym modelurozpoznawania zwyczajnych środków odwoławczych. Generalnie rzecz biorąc, w odniesieniu do polskich doświadczeń, można mówić w tym zakresie o modelach apelacyjnym i rewizyjnym. W klasycznej postaci system kontroli apelacyjnej obejmuje uchybienia zarówno w zakresie prawa, błędną ocenę okoliczności faktycznych, jak również błędy przy wymiarze sankcji karnej. W tej modelowej postaci sąd apelacyjny jest sądem ponownie przeprowadzającym dowody; w postępowaniu apelacyjnym wydaje się powtórnie orzeczenie, bez możliwości uchylenia zaskarżonego wyroku i przekazania sprawy do ponownego rozpoznaniaw pierwszej instancji. Tok procesu karnego jest w takim wypadku z reguły trójinstancyjny, a od wyroków sądu drugiej instancji przysługuje stronom kasacja do Sądu Najwyższego. Można wskazać szereg wad opisywanego modelu, a zwłaszcza: wydłużenie czasu trwania procesów, naruszanie zasady bezpośredniości przez to, że sąd apelacyjny orzekał w znacznej mierze również na podstawie dowodów przeprowadzonych przez sąd a quo, które nie były następnie ponawiane, możliwość zmniejszenia poczucia odpowiedzialności sędziego pierwszoinstancyjnego, skorowie on, iż poczynione przez niego ustalenia faktyczne mogą być ponownie dowodowo badane w instancji apelacyjnej. Rewizyjny model kontroli odwoławczej wprowadzono w polskim prawie krótko po zakończeniu drugiej wojny światowej, w okresie stalinowskiej reformy procedury karnej z lat 1949–1950. The subject of this study is to present the evidence collecting proceedings at the hearing of appeal in criminal matters. The key considerations in this regard have been preceded by a presentation of the Polish model of appeal proceedings, which can be described as a revisory. At the further stage of the study one can find the presentation of the classification of the means of conducting evidence by a judicial body in the form of the free and strict proof. Bearing in mind the extent of matter, in the further course of the consideration the focus is placed on the proceedings carried out at the hearing of evidence, with no look taken into the evidence issues carried out at the meeting. From the formal and structural point of view, the hearing of evidence at the trial before the court of appeal can be divided as follows: III. Taking of evidence on the merits as the free proof (Article 437 Paragraphs 1 and 2 of Code of Criminal Procedure) 1) which resulted in the non-change of facts 2) which resulted in the change of facts III. Taking of evidence on the merits in the form of the strict proof (Article 452 Code of Criminal Procedure): 1) which resulted in the non-change of facts 2) which resulted in the change of facts III. Taking of evidence as to the circumstances which are outside the essence of the matter: 1) in the form of the free proof 2) as the strict proof. The rest of the study aims at clarifying the issue what is the subject of proof in the appeal proceedings. In this regard, it was assumed that the subject of proof, regardless of what stage or type of case it is referred to, is the fact of the existence or nonexistence of a certain circumstance which is to be demonstrated in the chain of the evidence proving. Article 452 Paragraph 2 of Code of Criminal Procedure governs the strict proving process of the merit substance at the appeal hearing. However, if the court of higher instance does not utilize this possibility and merely reads the files, the free proving process on the merit substance is conducted as a result. In turn, beyond the “merit substance” in this sense are issues referring only to correctness of carrying out penal proceedings of the court a quo and the incidentally occurring issues taking shape before the court of higher instance. In relation to these issues, the Process Act does not express the type of proving, which means that both the strict and free chain of proving can be conducted. It should be noted that the “merit substance” as a collective category of the item of evidence on appeal, covers the circumstances surrounding the defendant’s legal liability (criminal and civil), in particular, to commit the offense, culpability, the legal act and the circumstances surrounding the imposition of criminal sanctions. Art 452 Paragraph 2 of Code of Criminal Procedure designates a legally acceptable limit on the taking of evidence as to the strict merits of the case at the hearing before the court of appeal. It provides for an exception to this general prohibition of Paragraph 1, and therefore, in its explanation the intensive interpretation shall not be carried out. Further on the content discusses the conditions in the taking of evidence by the court of appeal in accordance with Art 452 Paragraph 2 of Code of Criminal Procedure. Another issue that needed to be considered was whether the taking of evidence or evidences under this provision is – in the event of use of its circumstances – mandatory or optional. The study comes to an end with reflections on the changes regarding the admissibility of factual findings by the court of second instance without any evidence, and after close review at the hearing, in particular the impact of that evidence to alter the findings.